Implementasi Penguatan Sumber Daya Manusia di MAN 2 Ponorogo - Nasta'in Nasta'in (IJoIS: Indonesian Journal of Islamic Studies, 2022)
This study aims to describe the implementation of strengthening Human Resources at MAN 2 Ponorogo. The research method used is a qualitative case study model. Research data in the form of instruments and activities that support strengthening Human Resources at MAN 2 Ponorogo. Data collection techniques were carried out by observation and documentation. Meanwhile, data analysis was carried out by data reduction; data presentation; and concluding. The results showed that the implementation of strengthening Human Resources at MAN 2 Ponorogo on a macro basis was through (1) Signing of work contracts, (2) Formative Assessment of teacher performance and teacher self-evaluation, (3) Summative assessment of teacher performance, (4) Assessment of professional development. sustainable and (5) Teacher credit score assessment. Meanwhile, on a micro basis, through the program: (1) Every morning they take part in the Koran, memorize the Qur'an and read Asmaul Husna at the same time students read it, (2) Follow the teacher's special literacy, (3) Assign various activities and self-development, (4) Motivating and monitoring madrasah principals to participate in self-development activities, (5) peer tutorials, and (6) Special priority Human Resources development with additional budget and opportunities. And all of this is done with integrity.